Pembuktian Akun Palsu Terhadap Selebgram yang Diduga Melakukan Promosi Judi Online - Salsa Refalia; Boedi Prasetyo (Jurnal Hukum Lex Generalis, 2024)
This article aims to discuss the proof of fake accounts against celebrities who are allegedly involved in online gambling promotions, based on existing literature studies. Celebgrams or social media influencers are often the target of abuse by irresponsible parties, including in the form of fake accounts used to spread negative content, such as online gambling promotions. These fake accounts can be created with the aim of damaging the reputation of celebrities or tricking audiences into engaging in illegal activities. Proving fake accounts requires various methods, including technical analysis of digital footprints, identification of suspicious communication patterns, and proving the relationship between fake accounts and gambling promotion activities. In the case of online gambling promotion, this proof also involves the collection of digital evidence in the form of posts, comments, and other interactions that can indicate a criminal act. This process often involves working together between authorities and social media platform providers to identify sources and remove illegal content. Literature studies show that digital forensic analysis and social media monitoring are two effective approaches in identifying and proving the existence of fake accounts and their involvement in the promotion of illegal activities. Handling fake accounts and online gambling promotions requires cooperation between various parties, including law enforcement, platform providers, and the public, so that these illegal practices can be minimized.